High-fat diet-negative impact on female fertility: from mechanisms to protective actions of antioxidant matrices - Di Berardino, Chiara; Barceviciute, Urte; Camerano Spelta Rapini, Chiara; Peserico, Alessia; Capacchietti, Giulia; Bernabò, Nicola; Russo, Valentina; Gatta, Valentina; Konstantinidou, Fani; Donato, Marisa; Barboni, Barbara (Frontiers in Nutrition, 2024)
Excessive calorie intake poses a significant threat to female fertility, leading to hormonal imbalances and reproductive challenges. Overconsumption of unhealthy fats exacerbates ovarian dysfunction, with an overproduction of reactive oxygen species causing oxidative stress, impairing ovarian follicle development and leading to irregular ovulation and premature ovarian failure. Interest in biological matrices with high antioxidant properties to combat diet-related oxidative stress has grown, as they contain various bioactive factors crucial for neutralizing free radicals potentially preventing female reproductive health. This systematic review evaluates the female reproductive impact of biological matrices in mitigating oxidative damages induced by over calory habits and, in particular, high fat diets.A comparative approach among mammalian models was utilized to interpret literature available data. This approach specifically investigates the antioxidant mechanisms of biological matrices on early and late ovarian folliculogenesis, under physiological and hormone-induced female reproductive cycle. Adhering to the PRISMA 2020 guidelines, only English-language publications from peer-reviewed international indexes were considered. Results: The analysis of 122 publications meeting the inclusion criteria facilitated the identification of crucial components of biological matrices. These components, including carbocyclic sugars, phytonutrients, organosulfur compounds, and vitamins, were evaluated for their impact on ovarian follicle resilience, oocyte quality, and reproductive lifespan. The detrimental effects of oxidative stress on female fertility, particularly exacerbated by high saturated fat diets, are well-documented. In vivo studies across mammalian preclinical models have underscored the potential of antioxidants derived from biological matrices to mitigate diet-induced conditions. These antioxidants enhance steroidogenesis and ovarian follicle development, thereby improving oocyte quality. Additionally, discussions within these publications emphasized the clinical significance of these biological matrices, translating research findings into practical applications for female health.Further research is essential to fully exploit the potential of these matrices in enhancing female reproduction and mitigating the effects of diets rich in fatty acids. This requires intensified in vitro studies and comprehensive collection of in vivo data before clinical trials. The promotion of ovarian resilience offers promising avenues for enhancing understanding and advancing female reproductive health world-wide.